Evaluation of taVNS for extreme environments: an exploration study of health benefits and stress operationality - Le Roy, Barbara; Martin-Krumm, Charles; Gille, Adèle; Jacob, Sandrine; Vigier, Cécile; Laborde, Sylvain; Claverie, Damien; Besnard, Stéphane; Trousselard, Marion (Frontiers in Neurology, 2023)
Long-duration space missions will be a real challenge for maintaining astronauts' adaptability. Research on transcutaneous vagus nerve stimulation (taVNS) is expanding rapidly, and its modalities constitute a major research challenge. A growing number of reviews stress the need to validate biomarkers for monitoring effects, to enhance our understanding of the processes by which taVNS acts. The heart rate variability (HRV) appears to be a relevant candidate that informs on the autonomic nervous system (ANS). This is a promising technique to minimize the pathogenic effects of such large-scale missions and thus might be a relevant countermeasure. This study aims to investigate the impact of taVNS on cognitive, psychological, and physiological including ANS functioning and on the benefits of the number of taVNS sessions. 44 healthy participants were randomly assigned to one of two cross-over protocols: a unique (one taVNS, one sham) or a repeated session (three taVNS, three sham). Cognitive, psychological, and physiological measures were performed before (pre) and after (post) each intervention. Sleep monitoring was only recording before the first and after the last intervention in each protocol. Only for the repeated session, participants were allocated to two groups according to their parasympathetic activation gain during the three interventions: high parasympathetic delta (HPd) and low parasympathetic delta (LPd). Participants in the repeated session increase their HRV, cognitive performance as well as their sleep efficiency. Especially, the taVNS stimulation induced a higher parasympathetic activation and cardiac flexibility compared to the sham in the repeated session. Nevertheless, perception of stress may indicate a nocebo effect of the repeated session. The HPd profile had a higher interoceptive awareness, HRV highlighted by nonlinear measures, cognitive performance, but a decrease in some indicators of sleep efficiency compared to the LPd profile. The taVNS seems to induce positive health outcomes, especially when the stimulation is repeated three times per a week. Our findings highlight the benefits of parasympathetic activation during taVNS on psychophysiological and cognitive functioning. Further research is needed to validate these results on a large sample, using longitudinal measures among several months. This intervention appears promising as a countermeasure to extreme mission and occupations.